Upaya Guru dalam Memanfaatkan Media Pembelajaran sebagai Sarana Mengajar Bahasa Arab di Ponpes Modern Al-Mukmin Sukoharjo dan Al-Musyaddad Sragen. - Mubarok, Ahmad Dzaky; Aji, Hidayatur Rakhim Bhayu; Ghilman, Darwisy Muhammad (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
This research discusses the extent of teachers' efforts in utilizing learning media as a means of teaching Arabic and identifying various types of media used by teachers, such as YouTube videos, interactive applications, and other digital materials. Through a qualitative approach, information was collected from interviews with Arabic language teachers in two schools based on modern Islamic boarding schools, namely Ponpes Al-Mukmin Ngruki and Ponpes Al-Musyaddad Sragen. This research uses qualitative methods by means of descriptive analysis. The results showed that the efforts of teachers who are categorized as young teachers are more optimal in using learning media than senior teachers. Senior teachers prefer traditional methods to present learning in class. The use of appropriate learning media not only makes learning more interesting, but also helps students in understanding complex language concepts. In addition, this article also highlights the challenges teachers face in integrating learning media and provides recommendations for the professional development of masters in the use of educational technology. Thus, this article is expected to provide insights for educators and policy makers on the importance of utilizing learning media in Arabic language teaching, as well as encourage innovation in more effective teaching methods